2014
DOI: 10.1002/cssc.201402583
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Ammonia Poisoning by Addition of Platinum to Ru/α‐Al2O3 for Preferential CO Oxidation in Fuel Cells

Abstract: In polymer electrolyte fuel cell (PEFC) systems, small amounts of ammonia (NH3 ) present in the reformate gas deactivate the supported ruthenium catalysts used for preferential oxidation (PROX) of carbon monoxide (CO). In this study, we investigated how the addition of a small amount of platinum to a Ru/α-Al2 O3 catalyst (Pt/Ru=1:9 w/w) affected the catalyst's PROX activity in both the absence and the presence of NH3 (130 ppm) under conditions mimicking the reformate conditions during steam reforming of natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…We previously reported that the conversion of 130 ppm of NH 3 in the gas mixture was less than 30% and that the effluent gas included trace amounts of NO x over Ru/α-Al 2 O 3 . 31 A trace amount of NO 2 was detected in the effluent gas in our previous study; therefore, we surmised that NO 2 is related to deactivation of the Ru catalyst. However, during the operando IR investigation in the present study, no adsorption peaks assignable to NO 2 were observed.…”
Section: Resultsmentioning
confidence: 68%
See 4 more Smart Citations
“…We previously reported that the conversion of 130 ppm of NH 3 in the gas mixture was less than 30% and that the effluent gas included trace amounts of NO x over Ru/α-Al 2 O 3 . 31 A trace amount of NO 2 was detected in the effluent gas in our previous study; therefore, we surmised that NO 2 is related to deactivation of the Ru catalyst. However, during the operando IR investigation in the present study, no adsorption peaks assignable to NO 2 were observed.…”
Section: Resultsmentioning
confidence: 68%
“…Previously, we reported that the deactivation of Ru/α-Al 2 O 3 in the presence of NH 3 is enhanced with increasing O 2 /CO ratio. 31 Therefore, to emphasize the deactivation behavior of Ru/Al 2 O 3 and the difference between Ru/α-Al 2 O 3 and Pt/Ru/α-Al 2 O 3 , we carried out the operando study under flowing gas with CO/O 2 = 1/4 mol/mol. First, Ru/α-Al 2 O 3 was examined ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations